How Harmful is Smoking for Women? A Qualitative Study in Indonesia - Rosemary, Rizanna; Masrizal (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Introduction: In Indonesia, smoking is often perceived as a behavior associated with men, leaving women's perspectives on tobacco use largely unexplored. However, smoking has significant social, economic, health, and political implications for both genders. Despite the low reported smoking rates among women, their participation in tobacco control initiatives remains minimal. Female smokers face heightened social stigma compared to men, with stereotypes labeling them as socially unacceptable. This stigma often discourages quitting rather than deterring women from smoking in the first place, contributing to the underreporting of female smokers and making their numbers appear negligible. Objectives: This study aims to explore women’s experiences with smoking-related consequences in two locations, Banda Aceh and Jakarta. Findings indicate that both women who smoke and those whose partners are smokers encounter challenges in either starting or attempting to quit smoking. Additionally, beliefs about health and economic consequences serve as a common justification among smokers for not considering quitting. Methods: A qualitative study using semi-structured interviews seeks to explore the smoking-related experiences of women in two Indonesian cities, Jakarta and Banda Aceh. Results: The findings reveal that both female smokers and women with smoking partners face difficulties in initiating or maintaining cessation attempts. Additionally, perceptions of health and economic consequences often serve as justifications for avoiding efforts to quit smoking. Conclusion: The study found that socio-religious factors have a significant influence on women's experiences with smoking. Participants expressed beliefs about smoking tied to health and financial concerns, including the notion that outcomes like illness, death, and financial changes are predestined and beyond individual control (fatalism). This fatalistic perspective, shaped by their social and religious environment, hinders their efforts to quit smoking, making cessation more challenging.